In Vitro Nephrotoxicity and Permeation of Vancomycin Hydrochloride Loaded Liposomes - Nicole Papp; Jeffin Panicker; John Rubino; Gwendolyn Pais; Alexander Czechowicz; Walter C. Prozialeck; Brooke Griffin; Volkmar Weissig; Marc Scheetz; Medha D. Joshi (Pharmaceutics, 2022)
Drugs can be toxic to the fetus depending on the amount that permeates across the maternal–fetal barrier. One way to limit the amount which penetrates this barrier is to increase the molecular size of the drug. In this study, we have achieved this by encapsulating our model antibiotic (vancomycin hydrochloride, a known nephrotoxic agent) in liposomes. PEGylated and non-PEGylated liposomes encapsulating vancomycin hydrochloride were prepared using two different methods: thin-film hydration followed by the freeze–thaw method and the reverse-phase evaporation method. These liposomes were characterized by their hydrodynamic size and zeta potential measurements, CryoTEM microscopy, loading and encapsulation efficiency studies, in vitro release measurements and in vitro cytotoxicity assays using NRK-52 E rat kidney cells. We also determined the in vitro permeability of these liposomes across the human placental cell and dog kidney cell barriers. Vancomycin hydrochloride-loaded PEGylated liposomes (VHCL-lipo) of a size less than 200 nm were prepared. The VHCL-lipo were found to have the faster release of vancomycin hydrochloride and resulted in greater viability of NRK-52E cells. In vitro, the VHCL-lipo permeated the human placental cell and dog kidney cell barriers to a lesser extent than the free vancomycin hydrochloride. The data suggest a reduction in nephrotoxicity and permeability of vancomycin hydrochloride after encapsulation in PEGylated liposomes.